Assessment of social isolation and changes in Parkinson’s disease symptoms during the COVID-19 pandemic: A longitudinal study - Anish Mehta; Samuel Y.E. Ng; Shermyn X.M. Neo; Nicole S.Y. Chia; Ehsan S. Saffari; Thyagarajan Shivashanmugam; Xinyi Choi; Dede L. Heng; Z.Y. Xu; K.Y. Tay; W.L. Au; E.K. Tan; et al. (Clinical Parkinsonism & Related Disorders)
Background: COVID-19-related social restrictions provided an opportunity to evaluate the impact of social isolation on Parkinson’s disease. Objective: This study aimed to explore changes in social isolation and their associations with PD symptoms using the Lubben Social Network Scale-Revised (LSNS-R). Methods: Data from 80 participants of the Early Parkinson’s Disease Longitudinal Singapore cohort were collected from April 2019 to April 2023, covering the periods before and after the imposition of COVID-19 restrictions. Individuals with LSNS-R scores ≤ 24 were considered socially isolated. Data were stratified into strata 1 (improved LSNS-R scores) and strata 2 (worsened/unchanged scores). Linear regression was used to identify predictors of LSNS-R change, and MANCOVA was used to examine associations between LSNS-R change and motor/ non-motor symptoms. Results: Mean LSNS-R scores decreased (p = 0.014), and proportions of social isolation increased (p < 0. 001) during COVID-19 restrictions. However, 35 % showed improved LSNS-R scores, while 65 % had worsened/unchanged scores. The regression model was significant in strata 1 (R2 = 0.806, p = 0.001), with age, marital status, and social isolation status being significantly associated with change in LSNS-R scores. LSNS-R. Results of MANCOVA indicated that LSNS-R improvements in LSNS-R were significantly associated with outcomes (Roy’s Largest Root statistic = 126.638, p < 0.001), particularly for changes in PDQ8, HADS-Anxiety, and HADS-Depression scores. The regression model was not significant in strata 2 (R2 = 0. 279, p = 0.206), wherein motor and non-motor symptoms worsened. Conclusion: While worsening LSNS-R scores were associated with poorer outcomes, improvements in social networks were associated with improved non-motor symptoms and quality of life. These findings underscore the complexity of social isolation in PD and the need for targeted interventions.